2020
DOI: 10.1186/s12944-020-01211-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and its association with adiposity and dyslipidemia in Northwest China: results from cardiovascular risk survey in Xinjiang (CRS 2008–2012)

Abstract: Background: Hyperuricemia predisposes to gout, which may result in tophi, kidney stones, or urate nephropathy even kidney failure. Many metabolic risk factors and disorders has been recognized as a key risk factor contributing to development of hyperuricemia. Aim: To determine the prevalence of hyperuricemia and its association with adiposity and dyslipidemia. Methods: We recruited non-hospitalized participants (aged ≥35 years) in Xinjiang, a northwest part of China based on the Cardiovascular Risk Survey (CRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 58 publications
1
52
2
Order By: Relevance
“…Due to differences in research design between studies, the data extracted from the original studies were appropriately transformed before analysis [17]: (1) for studies that classified the participants into a high uric acid group and a control group, the extracted data were used for estimation without conversion; (2) for studies dividing the participants into multiple groups (or more than two groups), according to the definition criteria of hyperuricaemia [18], individuals meeting these standards were categorised into the high uric acid group, and the rest composed the control group; (3) hyperuricaemia was defined as > 7 mg/dl (416 μmol/L) for men and > 6 mg/dl for women, and the included studies were not grouped according to sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to differences in research design between studies, the data extracted from the original studies were appropriately transformed before analysis [17]: (1) for studies that classified the participants into a high uric acid group and a control group, the extracted data were used for estimation without conversion; (2) for studies dividing the participants into multiple groups (or more than two groups), according to the definition criteria of hyperuricaemia [18], individuals meeting these standards were categorised into the high uric acid group, and the rest composed the control group; (3) hyperuricaemia was defined as > 7 mg/dl (416 μmol/L) for men and > 6 mg/dl for women, and the included studies were not grouped according to sex.…”
Section: Discussionmentioning
confidence: 99%
“…With substantial changes in the traditional lifestyle, the consumption of high purine and high protein foods has increased, and hyperuricaemia has become a common clinical disease. The incidence of hyperuricaemia has shown a significant upward trend in recent years [1][2][3]. The prevalence of hyperuricaemia and gout in mainland China from 2000 to 2014 was 13.3% and 1.1%, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…HUA is considered to be a major risk factor of metabolic disorders after hypertension, hyperlipidemia, and hyperglycemia [ 8 ], and is considered to be the major pathological basis of gout, whereby approximately 5–12% of HUA patients have the possibility of developing gout [ 9 ]. Moreover, a large number of epidemiological studies have reported that HUA is closely related to diabetes, hypertension, obesity, cardiovascular disease, and kidney disease [ 10 , 11 , 12 , 13 ], which suggests that complications associated with HUA may increase in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the therapeutic effects of AM6545 and AM4113 antagonists in renal function might also result from the correction of the underlined MetS disorder. Several reports have demonstrated that dyslipidemia, including high triglycerides and high serum cholesterol levels, may contribute to kidney disease [ 41 , 42 ]. In our previous study, CB1 blockade with both antagonists produced a marked decrease in serum cholesterol and triglycerides, serum insulin, body weight, serum uric acid and liver TNFα together with increased adiponectin levels in the same MetS rat model [ 28 ].…”
Section: Discussionmentioning
confidence: 99%